STUDI KLINIS FORMULA JAMU ANTIHIPERGLIKEMIA TERHADAP FUNGSI HATI - Fajar Novianto; Agus Triyono (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2017)
ABSTRACT Salam leaf (Syzygium polyanthum), sambiloto (Andrographis paniculata), kayu manis (Cinnamomum burmani), and temulawak (Curcuma xanthoriza) is one of the jamu formulas are potentially developing as antihyperglycemic jamu in diabetes mellitus therapy. One of the important indicators of jamu formula safety is its toxicity on the liver function. The purpose of this study is to evaluate the safety of jamu formulas for hyperglycemic against liver function. This study is a clinical trial with a quasi-experimental design pre and post test design. The research conducted in jamu scientification clinic Hortus Medicus Tawangmangu on 45 healthy volunteers. The jamu formula is decoction of salam leaf (5 g), sambiloto (5 g), kayu manis (7 g), and temulawak (10 g). Jamu drinks three times a day. Forty-five healthy volunteers divided into three groups (each group consists of 15 healthy volunteers). Healthy volunteers (in group 1, II, and III) consuming jamu for 5, 10, and 15 days. Levels of SGOT and SGPT research subject reviewed before and after treatment. The difference in levels of SGOT and SGPT before and after treatment analyzed statistically with the paired t-test. The results showed there is no significance difference obtained at levels of SGOT and SGOT of healthy volunteers before and after jamu treatment on day 5, 10 and 15 (p > 0.05). This research concluded the antihyperglycemic jamu formula consisting of salam leaves (5 g), sambiloto (5 g), kayu manis (7 g), and temulawak (10 g) does not cause any signs of toxicity in the liver function. Key words: Clinical trial, hyperglycemia jamu formula, liver function